THE POSITION OF THE QURAN AS THE SOURCE OF ISLAMIC LAW - Suryani, Dewi Ervina; Asmuni, Asmuni; Syahnan, Muhammad (Al-Usrah : Jurnal Al Ahwal As Syakhsiyah, 2024)
The Qur'an is the primary source of various Islamic laws. As a source of law, the Qur'an contains a complete set of laws. In addition, the Qur'an provides guidance for humans regarding what they should do and refrain from doing in their daily lives. Meanwhile, the Sunnah is the second source of law after the Qur'an. Besides being a source of Islamic teachings that are directly related to the obligation to obey the Prophet Muhammad, it also functions as an explanation (bayan) for the expressions in the Qur'an. The purpose of this study is to determine the uniqueness of the Qur'an as divine revelation, as well as to determine the reasons or basis for the Qur'an being the main source of Islam. This research is a library research or literature research, which focuses on the analysis and interpretation of secondary data obtained from various sources, such as books, articles, and other documents. This research also uses a qualitative research approach, which focuses on a deep understanding of the phenomenon being studied. This study uses a hermeneutic research approach, which focuses on the interpretation and analysis of the text of the Qur'an and other sources related to Islamic law. This approach allows researchers to understand the context and meaning associated with the text of the Qur'an and how the text is used in legal decision-making. This study uses primary and secondary data sources. The primary data sources used are the Qur'an and Hadith, which are the main sources of law in Islam. The secondary data sources used are books, articles, and other documents related to Islamic law and the position of the Qur'an as a source of law.